Strategic Interaction of International Markets: An Application to the Dairy Market - Andrés José, Vargas (Desarrollo y Sociedad, 2001)
This paper studies the relation between the government’s objectives to sustain income in the dairy sector and the possibility to capture rent in the world market. To do this, two different governmental policies were considered: a direct export subsidy and a price discrimination scheme. These policies were analyzed under strategic and non-strategic scenarios. The results indicate that when there is non-strategic interaction and there exists a low opportunity cost of public funds, the two policies have the same effect on total welfare and lead to the same wealth transfer to producers. When there is a strategic interaction among producers, the price discrimination scheme leads to higher consumer welfare but lower producer benefit, being the net result on total welfare determined by the relative weights of the agents in the welfare function. From the producers’ point of view, the export subsidy is preferred to the price discrimination scheme when there is imperfect competition in the world market.